أهمية المشاركة الشعبية في التنمية الريفية المتكاملة في تجارب دول متقدمة ونامية - محمد الملا; عبيدة البريدي; طريف الجيوش (Tishreen University, 2017)
إن الكثير من مشكلات مجتمعاتنا المحلية (الريفية والحضرية) لن تحل إلا إذا شارك أبناء تلك المجتمعات في التخطيط لحلها حيث أنهم أعلم من غيرهم بواقع مجتمعاتهم بسبب المعايشة اليومية لتلك المشكلات فمن هنا جاء هدف البحث لإثارة اهتمام أفراد المجتمع الريفي بأهمية مشاركتهم في برامج التخطيط والتنمية لمجتمعاتهم ولتسليط الضوء أمام المخططين لبرامج التنمية الريفية على دور المشاركة الشعبية في هذه التنمية كونها متطلب رئيسي من متطلباتها وعلى مبادئ وسياسات هذه المشاركة بهدف العمل على تفعيل دورها لإنجاح التنمية الريفية. جاءت نتائج البحث لتبين أن المشاركة الشعبية هي إحدى وسائل زيادة كفاءة البيئة الاجتماعية وهي إحدى طرق بناء المجتمع الريفي حيث يستطيع السكان عن طريقها تحديد مشاكلهم والتعامل معها وذلك بالمشاركة في اتخاذ القرارات أثناء عملية التخطيط والبناء والإدارة للمشروعات وكذلك استثمار الإمكانات الأهلية المحلية (المالية والبشرية) مما يخفف الأعباء الملقاة على كاهل الدولة. Many of the our communities problems (urban and rural) will not be solved unless the citizens of these communities participate in planning to solve them, because they have the most knowledge about their communities because of their daily contact with these problems. Research target starts here to excite the attention of local community citizens to the importance of their participation in the planning and development programs of their communities, and highlight the role of neighbourhoods committees of local community participation for the planners of development programs, and the role of these committees in order to work out how to activate their role to be used in the development of the local community participation proce¬ss. Then the search results come to show that the local community participation is one of tools that increase the social environment efficiency, and one of the ways that build the community which helps people to identify their problems and deal with them by the participating in the decision-making during the process of planning, construction, management of projects and investment of the local civil abilities (financial and human) in order to decrease the state burdens